2012
DOI: 10.17660/actahortic.2012.938.4
|View full text |Cite
|
Sign up to set email alerts
|

Seed Bacterial Endophytes: Common Genera, Seed-to-Seed Variability and Their Possible Role in Plants

Abstract: Seeds contain endophytic bacteria that may be transmitted from generation to generation. Some of these bacteria can benefit plant growth and defense against abiotic and biotic stresses. Little is known however about the mechanisms of bacterial colonization of seeds and their transmission from generation to generation in host plants. In this study we have demonstrated that individual seeds of maize (Zea mays L.) taken from the same cob and bean seeds (Phaseolus vulgaris L.) from different pods and within indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 61 publications
(65 reference statements)
2
18
0
Order By: Relevance
“…This observation is consistent with similar trends reported elsewhere (Ganley and Newcombe 2006;Truyens et al 2015). It is reported that the majority of seedassociated bacterial endophytes belong to Proteobacteria such as Bacillus, Staphylococcus, Pseudomonas and Pantoea (Rosenblueth et al 2012;Truyens et al 2015). The seed-associated D r a f t endophytes reported in this study belonged to the above taxa.…”
Section: R a F Tsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is consistent with similar trends reported elsewhere (Ganley and Newcombe 2006;Truyens et al 2015). It is reported that the majority of seedassociated bacterial endophytes belong to Proteobacteria such as Bacillus, Staphylococcus, Pseudomonas and Pantoea (Rosenblueth et al 2012;Truyens et al 2015). The seed-associated D r a f t endophytes reported in this study belonged to the above taxa.…”
Section: R a F Tsupporting
confidence: 93%
“…Cultivar specificity to bacteria and fungal endophytes has been reported in several crops including Cannabis (Bailey et al 2005;Rasche et al 2006;Rosenblueth et al 2012;Wearn et al 2012;Winston et al 2014). Hence, studies on biodiversity and cultivar specificity of cultured endophytic microorganisms associated with hemp merit further research.…”
Section: R a F Tmentioning
confidence: 99%
“…The cultivation of seed endophytes is also challenging because of the specific habitat they are derived from. Seed endophyte population sizes range from 55 colony‐forming units (cfu) per gram in bean (Rosenblueth et al ., ) to as high as 10 7 cfu g −1 in rapeseed (Granér et al ., ). In general, common bacterial genera reported in seeds of very different plant species are Bacillus and Pseudomonas .…”
Section: Frequently Reported Bacterial Seed Endophytesmentioning
confidence: 99%
“…In contrast, neutral processes for seed assembly may include dispersal-driven colonization of microbiota to flowers that then are transmitted to the seed, for example via air or rain events. Cultivation-dependent approach performed on seed endophytes in corn and common bean showed substantial variability in the populations recoverable from the same cob and pod, respectively [71], therefore suggesting that these plants may not provide a strong selective environment for seed microbiota.…”
Section: Current Opinion In Microbiologymentioning
confidence: 99%